Peran pendidikan dalam meningkatkan kesetaraan gender di Indonesia pasca pandemi COVID 19 - Firdaus, Mohammad; Khasanah, Nur (Jurnal Pendidikan Agama Islam, 2025)
Gender equality is one of the main pillars of sustainable development, especially in developing countries like Indonesia recovering from the COVID-19 pandemic. This article examines the role of education in promoting gender equality post-pandemic through literature analysis and current empirical data. Education is considered a key instrument to change social norms, increase access to economic opportunities, and reduce gender stereotypes exacerbated by remote learning during the pandemic. Based on a review of Indonesia's education policies, such as the 2013 Curriculum and post-COVID education recovery programs, education can facilitate women's participation in STEM fields and leadership. However, challenges such as increased domestic burdens on women and digital divides remain obstacles. This article recommends strengthening inclusive curricula, equitable technology access, and teacher training to promote broader gender equality in the post-pandemic era.